2018
DOI: 10.1111/jocd.12771
|View full text |Cite
|
Sign up to set email alerts
|

An autologous protein gel for soft tissue augmentation: in vitro characterization and clinical evaluation

Abstract: This novel injectable formulation has desirable mechanical and bioactive properties for 3D tissue regeneration and might offer a safe and effective treatment for depressed areas of the skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 51 publications
0
18
0
4
Order By: Relevance
“…Once injected, PRGF‐gel presents an hyperechogenic nodule pattern as its echographic hallmark. Ultrasound examinations performed in other studies revealed an augmentation of the dermo‐epidermal echodensity and an overall dermal thickness increase indicating newly synthesized components of the intercellular matrix and collagen fiber disposition . Post‐treatment results showed an increased echointensity of cutaneous connective tissue along with a decrease in the total hypoechoic areas .…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Once injected, PRGF‐gel presents an hyperechogenic nodule pattern as its echographic hallmark. Ultrasound examinations performed in other studies revealed an augmentation of the dermo‐epidermal echodensity and an overall dermal thickness increase indicating newly synthesized components of the intercellular matrix and collagen fiber disposition . Post‐treatment results showed an increased echointensity of cutaneous connective tissue along with a decrease in the total hypoechoic areas .…”
Section: Discussionmentioning
confidence: 74%
“…Ultrasound examinations performed in other studies revealed an augmentation of the dermo‐epidermal echodensity and an overall dermal thickness increase indicating newly synthesized components of the intercellular matrix and collagen fiber disposition . Post‐treatment results showed an increased echointensity of cutaneous connective tissue along with a decrease in the total hypoechoic areas . In fact, some authors have described a reduction of the subepidermal low echogenic band (SLEB) after PRGF treatment, suggesting the potential of this technology for activating the cell turnover that might improve the tone and elasticity of skin thereby counterbalancing chronological aging mechanisms which slow metabolic activity and render skin atrophy .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This formulation provides a greater volume stability and long‐term shape maintenance that offers optimal mechanical stability for cutaneous defect viscosupplementation 12 . Recent clinical findings suggest that Endoret‐Gel acts as a volume enhancer biomaterial that reduces wrinkles and static lines along with a marked lifting effect that ultimately balances the cutaneous profile 13 …”
Section: Introductionmentioning
confidence: 99%
“…Há uma evidente busca por procedimentos que sejam seguros, toleráveis e pouco invasivos. Nos últimos anos, a terapia com Plasma Rico em Plaquetas emergiu como uma modalidade de tratamento na área da dermatologia e estética devido à capacidade de induzir o crescimento celular na pele, retardando e atenuando o processo de envelhecimento (AMINI et al, 2015;FEDYAKOVA et al, 2018). O plasma rico em plaquetas é um concentrado de plaquetas derivado do sangue autógeno obtido pelo processo de centrifugação.…”
Section: Introductionunclassified